Efficacy of Mentalization-Based Group Therapy for Adolescents: A Pilot Randomised Controlled Trial. (April 2018) - Eliasson, Emma; Graham, Jessica; Thompson, Alice; Happer, Rachel; Butler, Maeve; Schwannauer, Matthias; Griffiths, Helen; Duffy, Fiona
No abstract available